Child Labor Issues and Relations with Human Rights - Faridah, Siti; Afiyani, Laila (Universitas Negeri Semarang, 2019)
Consists Over time, the exploitation of child labor in Indonesia is increasing every year. This is due to low economy and education which forces children to work and help their parents financially. Juridically, Indonesia has regulations governing child labor as stated in the labor law. This is intended so that children's rights are not ignored but are still protected by the government. However, the rules that have existed from time to time are not in accordance with the complexity of society that continues to develop until now. So that it is as if the rules in force do not have the power to regulate the order of society. According to the Convention on the Rights of the Child, children have the right to be protected from all forms of economic exploitation and from all forms of work that is hazardous and interferes with the child's education, health, physical, mental, spiritual, moral and social aspects. In this case, there are three approaches to looking at the problem of child labour, namely elimination, protection and empowerment.